Socio-economic Study of Karbi Tribe of Silonijan - a Case Study in Karbi-anglong District of Assam - Singh, Jasbir; Chandra, Anup; Saikia, Hem Chandra; Thakuria, G. (Indian Forester, 2002)
A socio-economic study was conducted in four villages of Karbi Anglong District of Assam. Cent percent households were surveyed. Sex ratio (females per 1000 males) was found very high among the shifting cultivators. Literacy rate and annual income and saving is very low among the shifting cultivators. It is revealed that overall socio-economic condition of the shifting cultivators is very poor. Better educational levels and adequate efficient infrastructural facilities will provide impetus to the positive growth of socio-economics of the shifting cultivators. In addition to this, sustainable land use system like agro-forestry and forest based industry, cash crops, etc. can be introduced in the jhum area. It will not only improve the ecology of the area but also will help in upliftment of shifting cultivators.